Answer:
Half of a number is 15
Step-by-step explanation:
First of all, add commas between each option so it's easier to read I had a hard time figuring out what the options were because of this.
An equation is a statement that the values of two mathematical expressions are equal. An expression is a collection of symbols that jointly express a quantity. This means there has to be an equal sign when the phrases are put into numerical form.
Twice as much as a number: 2X
12 less than a number: X - 12
Half of a number is 15: X/2 = 15
The difference of 20 and a number: 20 - X
As you can see, only one of these phrases is an equation by definition, and that is X/2 = 15, or half of a number is 15. That's because it's the only one that values two expressions as equal.
we have that
−4+8−16+32−.....
a1=-2*(-2)-----> -4
a2=-4*(-2)-----> +8
a3=+8*(-2)-----> -16
a4=-16*(-2)----> +32
a5=+32*(-2)----> -64
a6=-64*(-2)-----> +128
a7=+128*(-2)-----> -256
The sum of the first 7 terms of the series is
<span>[a1+a2+a3+a4+a5+a6+a7]-----> [-4+8-16+32-64+128-256]------->
-172</span>
<span>
the answer is -172</span>
Answer:
Twenty-seven and a half million metric tons of apples are eaten fresh.
Step-by-step explanation:
The amount of metric tons of apples that are eaten fresh is equal to the half of the total amount of metric tons. That is:
![m = \frac{55,000,000\,m-ton}{2}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B55%2C000%2C000%5C%2Cm-ton%7D%7B2%7D)
![m = 27,500,000\,m-ton](https://tex.z-dn.net/?f=m%20%3D%2027%2C500%2C000%5C%2Cm-ton)
Twenty-seven and a half million metric tons of apples are eaten fresh.
Hey there!
Here is your question -
![n+12=4](https://tex.z-dn.net/?f=n%2B12%3D4)
In this equation, you're looking for n alone. To keep the variable alone, you have to do the opposite of what's happening to the variable.
In this equation, 12 is being added to n. The opposite of that is subtracting 12.
Subtract 12 from both sides -
![n+12-12=4-12 \\ n=-8](https://tex.z-dn.net/?f=n%2B12-12%3D4-12%20%5C%5C%20n%3D-8)
Your answer is -8.
Hope this helps! :)
Answer:
dT/dt = k(L-Lt)
Step-by-step explanation:
Let the rate of growth in length be dL/dt
The difference between the current length L and the asymptotic length Lt will be expressed as L-Lt
If the rate of growth in length of an individual fish is proportional to the difference between the current length L and the asymptotic length Lt, this is expressed as;
dT/dt ∝ L-Lt
dT/dt = k(L-Lt) where
k is the proportionality constant
Hence the differential equation that expresses this idea is written as;
dT/dt = k(L-Lt)